Adsorption of Reactive Blue 171 from Aqueous Solution using Low Cost Activated Carbon Prepared from Agricultural Solid Waste: Albizia amara - K. Anitha; P. S. Syed Shabudeen; S. Karthikeyan; N.Aruna devi (Carbon: Science and Technology, 2015)
The adsorption of Reactive Blue 171 (Reactive Dye) from aqueous solution using activated carbon prepared from Albizia amara pod shell waste as an adsorbent have been carried out. The experimental adsorption data fitted reasonably well to Langmuir and Freundlich adsorption isotherms. Kinetic parameters as a function of Initial dye concentration have been calculated and the kinetic data were substituted in Pseudo First Order, Elovich and Pseudo Second order equations. A probable explanation is offered to account for the results of kinetic study. The thermodynamic parameter enthalpy change (∆H) suggests the exothermic nature of absorption of Reactive Blue 171 onto activated Albizia amara pod shell waste carbon.